Digital Political Stage: An Analysis of the Hyperreality of Prabowo–Gibran’s Social Media Gimmick Campaign in the 2024 Election - Saputro, Moh. Adil; Prakasita, Ajeng Widya; Rahmat, M. Basuki; Fitria, Vany (Indonesian Journal of Political Studies, 2025)
Digital platforms have transformed political campaign models and created spaces where the boundaries between reality and illusion become blurred. This study analyzes the social media gimmick strategy used by the Prabowo-Gibran pair in the 2024 election, highlighting how the gimmick is not only a tool of political communication, but also builds hyperreality. Using the theoretical framework of simulacra and simulation from Jean Baudrillard, this study reveals how political communication strategies through gimmicks on social media can build a hyperreal image, where campaign elements become more "real" than actual political reality. A descriptive qualitative approach was used to analyze the data obtained from the publication of PT Indonesia Indicator using content analysis. The results of this study show that political gimmicks are not just a strategy to attract the attention of voters, but have developed into a hegemonic instrument that forms a new reality that is independent of the real reality. In this context, democracy faces serious challenges, when political representation relies more on visual appeal and social media narratives, then political substance can be displaced by pseudo-illusions designed to drive and control public opinion.